Web-Based Structural Analysis Tool for Simply Supported Beam Using Python - Purwitasari, Kartika; Cahyani, Kharisma Nur; Yoganata, Yehezkiel Septian; Safitri, Mona Shinta; Rahmawan, Fauzi Akbar; Jannah, Miftakhul (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Structural analysis is essential in civil engineering to ensure the' safety, stability, and performance of load-bearing elements such as beams. Conventional approaches—such as manual calculations or commercial software—often involve high costs, limited accessibility, or steep learning curves. This study presents a web-based computational tool for analyzing simply supported beams, developed in Python to deliver accurate, real-time results through an interactive interface. The tool utilizes fundamental static equilibrium equations to calculate support reactions, shear forces, and bending moments in the simply supported beam subjected to point and uniformly distributed loads. Python’s numerical and visualization libraries enable the automated generation of shear force and bending moment diagrams, input validation, downloadable CSV outputs, and adjustable parameters. Validation consisted of three stages: comparison with analytical hand calculations, benchmarking against Tekla Structural Designer (Educational License), and a usability survey conducted among 67 participants from academic and professional backgrounds. The tool’s results matched reference calculations, and user feedback highlighted high accuracy, clarity, and educational value. This open-access platform offers an effective solution for educational use. Future development will focus on extending features such as analyzing more complex structures under various loading conditions, performing deflection analysis, and mobile compatibility.